FIGURE 1 in The genus Callitriche (Plantaginaceae: Callitricheae) in South America - Lansdown, Richard V.; Hassemer, Gustavo (Zenodo, 2021)
FIGURE 1. Fruits of South American Callitriche: a—C. albomarginata, b—C. antarctica, c—C. berteroana, d—C. ciliata, e—C. ciliata showing fibrils, f—C. concinna, g—C. dacryoidea, h—C. deflexa, i—C. ecarinata, j—C. hegelmaieriana, k—C. heterophylla, l—C. heteropoda. Published as part of Lansdown, Richard V. & Hassemer, Gustavo, 2021, The genus Callitriche (Plantaginaceae: Callitricheae) in South America, pp. 85-118 in Phytotaxa 501 (1) on page 88, DOI:10.11646/phytotaxa.501.1.3, http://zenodo.org/record/5424744